Local currencies -- pro or counter cyclical? - Tomány, Lubomír (2011)
This work focuses on local (complementary) currencies. Their usage and appearance throughout history indicate counter-cyclicity with Great Depression and Argentine recession in 2002 as leading examples. Also previous research of Stodder (2009) proved counter-cyclicity in usage of Swiss complementary currency WIR. However, USA at the beginning of 90' and Germany after year 2000 experienced new wave of local currencies without being accompanied by any severe crisis. Have they become pro-cyclical? I tried to answer this question empirically with simple econometric model using macroeconomic indicators as explanatory variables. Results showed that number of new local currencies is in Germany pro-cyclical which supports previous works about regional distribution of currencies in Germany. Results from USA are inconclusive but indicate rather counter-cyclicity. In both countries was proved positive correlation with amount of already working currencies.